The management of soft tissue tumours of the abdominal wall. Issue 9 (September 2017) - Smith, H.G.; Tzanis, D.; Messiou, C.; Benson, C.; van der Hage, J.A.; Fiore, M.; Bonvalot, S.; Hayes, A.J.
Abstract: Background: Soft tissue tumours of the abdominal wall account for approximately 10% of all soft tissue tumours. Tumours at this site comprise a heterogeneous group of pathologies with distinct clinical behaviours and responses to treatment. The management of these tumours has largely been extrapolated from studies of soft tissue tumours at other sites. This review aims to summarise the existing data relating to abdominal wall tumours and suggest principles for managing soft tissue tumours at this site. Methods: Relevant articles were retrieved from a comprehensive literature search using the PubMed database. Key words included abdominal wall, soft tissue tumours, surgery, radiotherapy and chemotherapy. No restrictions on publication date were used. Results: The most common pathologies presenting in the abdominal wall are desmoid tumours, soft-tissue sarcoma and dermatofibrosarcoma protuberans (DFSP). Desmoid tumours should be managed with an initial period of observation, with surgery reserved for progressive lesions. Surgery should be the primary treatment for soft-tissue sarcomas and DFSP, with radiotherapy reserved for large-high grade tumours and preferentially given pre-operatively. Conclusions: Abdominal wall tumours are rare and should be managed in centres with experience in the management of soft tissue tumours. Management should be tailored to the biological behaviour of specific pathologies.